The restructuring of labour in Brazil in the 2000s: flexible work and the precarisation of working life. (1st July 2011) - Giovanni Alves,
Abstract : This article argues that the precarisation of employment that has taken place in Brazil since the 1990s has been fundamentally different in kind from earlier forms of precariousness, which took place outside the formal economy. The new forms of precariousness are taking place within the sphere of the economy controlled by transnational corporations. Although they have only reached critical mass during the 2000s, the ground was prepared by 'post neoliberal' restructuring, including labour law reforms, that took place in Brazil during the 1990s and introduced new forms of flexible working. The article argues that the new condition of labour now emerging in Brazil, which is a structural feature of labour under global capitalism, is characterised by psychosocial dynamics that cause: first, class desubjectivation; second, a 'seizure' of the waged worker's subjectivity; and third, the reduction of living labour to the status of a workforce treated as goods. Comprehending these changes necessitates a related change in the theoretical and methodological framework in which the precariousness of work is studied, one that incorporates within its scope the issues of workers' health and the quality of working life.